Global Logistics Efficiency After COVID-19: A Cross-Country Analysis Using the Logistics Performance Index - Bayraktar, Erkan; Zaim, Selim; Güdelek, Mehmet; Gölgeci, İsmail (Taylor & Francis, 2025)
This study analyses the World Bank’s Logistics Performance Index (LPI) to quantify changes in logistics performance before and after COVID-19, using a slack-based measurement (SBM) model of data envelopment analysis (DEA) and the Malmquist Index (MI), which indicates efficiency changes over time. The LPI analysis shows performance gains, but challenges in timeliness and international shipments. The SBM-DEA model indicates efficiency improvements mainly through technological advancements. After the pandemic, the decline in efficiency in customs operations and international shipments signals a need for streamlined procedures and cost reductions. The analysis also shows that the post-pandemic recovery varied by region. This study contributes to the theory by showing how dynamic capabilities and institutional resilience influence logistics adaptability and widen global performance gaps. Informed by the resource-based view and dynamic capabilities theory, it advises policymakers to enhance logistics infrastructure, modernise customs, and reduce costs to tackle postpandemic challenges in underperforming regions.
Keywords: Global logistics performance; Logistics performance index (LPI); Data envelopment analysis (DEA); Malmquist index (MI); Efficiency; Pandemic